2018
DOI: 10.1016/j.toxrep.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Morphological alterations induced by the exposure to TiO2 nanoparticles in primary cortical neuron cultures and in the brain of rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Animal were euthanized after different time intervals (4 days, 1 and 2 months) in order to observe acute and chronic toxicological effects of TiO 2 . The range of doses used in our study was in accordance with other toxicological and pharmacokinetic studies [22, 3134]. Morphological and physiological damage induced by a single i.p.…”
Section: Discussionsupporting
confidence: 66%
“…Animal were euthanized after different time intervals (4 days, 1 and 2 months) in order to observe acute and chronic toxicological effects of TiO 2 . The range of doses used in our study was in accordance with other toxicological and pharmacokinetic studies [22, 3134]. Morphological and physiological damage induced by a single i.p.…”
Section: Discussionsupporting
confidence: 66%
“…The influence of TiO 2 on the central nervous system (CNS) is gaining attention recently. Valentini et al investigated the toxicity of TiO 2 -NP to the cortical neuron cultures and in the brain of rats, reported the clear impact of TiO 2 -NP on the neuronal cells and rat brain, and indicated the new evidences of TiO 2 -NP toxicity in CNS [32].…”
Section: Resultsmentioning
confidence: 99%
“…Animal experiments, especially in rodents, are being conducted to study the effects of titanium oxide nanoparticles on the human body. In these experiments, titanium was overdosed in rats and the distribution of titanium in the liver, spleen, bone marrow, lungs, brain, and kidneys and titanium-related problems were found in each tissue [32, 33, 90]. In particular, lung problems, cytotoxic reactions, inflammation reactions, fibrosis, and tumors were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Valentini et al observed a characteristic phenotype of activated microglia cells caused by the presence of TiO 2 NPs. Their morphological changes, such as the larger size and formation of membrane protrusions typical of phagocytosis, indicated the uptake of TiO 2 NPs through this process [73].…”
Section: Cellular Uptakementioning
confidence: 99%